DAMPAK PSIKOLOGIS KEKERASAN SEKSUAL DAN IMPLIKASINYA TERHADAP MOTIVASI BELAJAR - Reni Rahmawati; Asep Sahrul Gunawan (STKIP Subang, 2026)
Sexual violence is a serious issue that has widespread impacts on victims' psychological conditions, particularly in the context of education. This study aims to analyze the psychological impacts of sexual violence on learning motivation, identify factors that exacerbate these conditions, and examine strategies to address them. The research employs a Systematic Literature Review (SLR) method by analyzing 12 SINTA-indexed journal articles published between 2020 and 2025, and 2 relevant academic books. The findings indicate that the psychological impacts of sexual violence are multidimensional, encompassing emotional, cognitive, social, and behavioral aspects that significantly affect victims' learning motivation. Factors such as lack of social support, social stigma and victim blaming, unsafe educational environments, and limited psychosocial assistance contribute to the decline in learning motivation. Effective interventions include psychological support, the implementation of Psychological First Aid (PFA), strengthening the role of educational institutions in creating safe environments, and enhancing social support from family and peers. A holistic and integrated approach is essential in supporting psychological recovery and sustainably improving victims' leaming motivation.